(untitled) (Journal of Hama University, 2021)
In this research, the risks associated with the safety of cake products in terms of physical, chemical and biological hazards on a continuous industrial production line for cream filled cake were studied. This study allowed identifying all potential risks associated with this industry, which were represented by five basic stages within the manufacturing line, which are “baking, filling, dipping, cooling and packaging”. The study also showed the mechanism of applying the HACCP system by adopting the risk analysis method by following the decision tree methodology and assessing the risk levels, in addition to setting procedures for controlling critical limits, and adopting the necessary corrective actions measures in cases of deviation from the approved limits of critical points.The risk of fungi formation on the surface of the cake product manufactured during the shelf life has been fully controlled by maintaining water activity lower than 0.74 by balancing cake recipe and controlling the baking conditions, which achieves stability of the product and complete free-fungi cakes during storage.